Study design of herbal medicine clinical trials: a descriptive analysis of published studies investigating the effects of herbal medicinal products on human participants - Nut Koonrungsesomboon; Chotiwit Sakuludomkan; Mingkwan Na Takuathung; Preeyaporn Klinjan; Suphunwadee Sawong; Pathirage Kamal Perera (BMC Complementary Medicine and Therapies)
Abstract Background Increasing global interest in natural therapies has led to a rise in the use of herbal medicines for managing various ailments. However, concerns about scientific evaluation have prompted a study aiming to assess the study design of herbal medicine clinical trials. This study aimed to provide a descriptive overview of the study design, characteristics, and methodologies of contemporary herbal medicine clinical trials. Materials and methods The study reviewed herbal medicine clinical trials published between 2019 and 2022 in five electronic databases: PubMed, Embase, Web of Sciences, Scopus, and the Cochrane Library. Data extraction included study characteristics, intervention details, study design, outcome measures, trial phases, blinding, and other relevant information, with descriptive analyses presented. The term ‘herbal medicines’ in this study refers to herbs, herbal materials, preparations, and finished products containing active ingredients from plant parts or their combinations. Results Out of the initially identified 5,918 records, 1,517 articles were eligible for inclusion in the study. The majority of herbal medicine clinical trials were conducted in Asian countries, covering a range of diseases. A randomized, double-blind, parallel design with a 1:1 allocation ratio was frequently employed, along with the common use of placebos across all trial phases. Capsules were the most common dosage form. The median number of human participants varied across trial phases, ranging from 50 in Phase 1 to 240 in Phase 4. Conclusions The analysis observed that herbal medicine clinical trials employed randomized, double-blind, parallel designs, and the widespread use of placebo. Our observations provided valuable insights into the evolving landscape of herbal medicine clinical trials.